Getting started with cloud computing : a LITA guide - Corrado, Edward M.; Moulaison, Heather Lea.; Library and Information Technology Association (U.S.) (New York : Neal-Schuman Publishers, 2011)
The book is designed to explain cloud computing as it pertains to the library community.
Includes bibliographical references and index.
uaj 09/05/13
Loans
Keywords: Cloud computing